MiRNA-186-5p Exerts an Anticancer Role in Breast Cancer by Downregulating CXCL13. (25th February 2022) - Wang, Yulong; Hu, Shaojun; Zhang, Hongbin; Zhang, Chenxin; Lian, Qixin; Jiao, Yu; Zhou, Yu
Abstract : The aim of this study is to illustrate the biofunctions of miRNA-186-5p level in breast cancer (BCa) and to explore the underlying mechanisms. Levels of miRNA-186-5p in BCa tissues and adjacent normal ones were determined. Association of miRNA-186-5p with pathological parameters and prognosis in BCa patients was analyzed. Luciferase assay was conducted for the prediction of the interaction between miRNA-186-5p and CXCL13. Their mutual interaction in influencing the proliferative potential of BCa was finally explored. Results showed that miRNA-186-5p expression was downregulated in BCa cell lines and tissues. MiRNA-186-5p overexpression could attenuate proliferative ability in BCa cells. A direct and negative correlation was identified between miRNA-186-5p and CXCL13. In addition, their mutual interaction was coresponsible for the malignant development of BCa. In BCa patients, miRNA-186-5p level was remarkably associated with tumor size and tumor staging, rather than other pathological parameters. Low level of miRNA-186-5p predicted a poor prognosis in BCa. Downregulated miRNA-186-5p in BCa is linked to tumor size, tumor staging, and prognosis. miRNA-186-5p downregulates CXCL13 by binding CXCL13 3′UTR in BCa cells. Overexpression of CXCL13 can significantly neutralize the inhibitory effects of miRNA-186-5p on BCa proliferation.